2022
DOI: 10.7150/thno.72192
|View full text |Cite
|
Sign up to set email alerts
|

TRIB1 regulates tumor growth via controlling tumor-associated macrophage phenotypes and is associated with breast cancer survival and treatment response

Abstract: Molecular mechanisms that regulate tumor-associated macrophage (TAM) phenotype and function are incompletely understood. The pseudokinase TRIB1 has been reported as a regulator of macrophage phenotypes, both in mouse and human systems. Methods: Bioinformatic analysis was used to investigate the link between TRIB1 expression in breast cancer and therapeutic response to chemotherapy. In vivo models of breast cancer included immune-competent mice to characterize the consequences of altered (reduced or elevated) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Kim et al . [ 37 ] have demonstrated that TRIB1 regulates tumor growth and is associated with breast cancer survival and treatment response. In addition, BACH2 also directly regulates TF XBP1, which can reduce the proliferation and stemness of cancer cells [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al . [ 37 ] have demonstrated that TRIB1 regulates tumor growth and is associated with breast cancer survival and treatment response. In addition, BACH2 also directly regulates TF XBP1, which can reduce the proliferation and stemness of cancer cells [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…We identified 80 sgRNAs that meet one (65), two (17) or all (2) of these criteria (Supplementary Table 3). Among the genes targeted by these sgRNAs are those involved in cell motility (Tesk1, Pkn1 and Mylk4) [20][21][22] , nucleotide homeostasis and metabolism (Prps1, Prps2, Adck2 and Nme8) 23 or modulation of insulin sensing (Trib1 and Pip4k2c) [24][25][26] or function as tumor suppressors (Fgfr3) 27 , such that the loss of these genes would promote hallmarks of metastasis. The top hit in this screen by all applied metrics was loss of Pip4k2c, which encodes phosphatidylinositol-5-phosphate 4-kinase type 2 gamma.…”
Section: Crispr Screens Reveal Determinants Of Lmmentioning
confidence: 99%
“…TRIB1 reduces DR5 protein levels in breast cancer cells through its elevated NF-кB signaling, thus decreasing TRAIL-induced apoptosis [36]. Heightened expression of TRIB1 in tumor associated macrophages (TAMs) influences the breast cancer tumor microenvironment by regulating oncogenic cytokine expression [73].…”
Section: Breast Cancermentioning
confidence: 99%
“…In primary GBM cells, TRIB1 causes upregulation of the ERK and Akt pathways and modulation of p53 function through COP1 and HDAC1, further contributing to therapy resistance [34]. TRIB1 negatively regulates the anti-tumor cytokine IL-15 in TAMs in breast tumors, causing a decrease in T-cells that promote anti-tumor responses [73]. TRIB1 has been identified as a negative regulator of T-cell receptor (TCR) signaling via its interaction with MALT1, a TCR activator, leading to disruption of MALT1 signaling complexes responsible for optimal T cell activation and function [49].…”
Section: Role Of Trib1 In Cancer Therapy Resistancementioning
confidence: 99%